Corrigendum: Diagnostic use of abdominal ultrasound in detecting extrapulmonary tuberculosis or lymphoma in an HIV-endemic region - Ellouise C. Adams; Katherine Antel; Jenna L. Bailey; Karryn L. Brown; Dharshnee R. Chetty; David Richardson; Estelle Verburgh (Southern African Journal of HIV Medicine, 2025)
No abstract availabe.